Ready, set, mission! - Cosby, Nate. (New York : Disney Press, 2009)
The members of the G-Force - gerbils Darwin, Juarez, and Blaster, and Mooch the fly - infiltrate the billionaire Saber's house during a party to steal a computer file undetected.
At head of title: Disney G-Force.
Keywords: Gerbils -- Fiction; Animals -- Fiction; Espionage -- Fiction; Adventure and adventurers -- Fiction; Spy stories; Adventure fiction